ICT utilization among school teachers and principals in Malaysia - Hoque, Kazi Enamul; Razak, Ahmad Zabidi Abdul; Zohora, Mosa Fatema (2012)
The purpose of this research was to find the areas of ICT utilization among teachers and principals of Malaysian schools. Quantitative method was used in this study with a representative sample of 260 school teachers, teachers-supervisors and principals. The finding of the research demonstrates that 84% of the teachers are not aware of national ICT policy though it exists. Finding shows that most of the schools (80%) do not have ICT policy at the school level though the facilities and equipment of ICT are available in most Malaysian schools. Almost all the teachers have a high level of skills in using computer and profoundly the basic skills needed for teachers in IT are attained by all the teachers. Likewise, 95% schools have photocopy machines and scanners while the multimedia projector is available in 85% schools. Besides, 72% schools are equipped with a video camera, overhead projector and laptop. However, it is interesting that their expertise and skills are not integrated with educational management or with teaching/ classroom purposes. Rather they are used for daily administrative purposes. The findings of the study will benefit the policy makers of developing countries, Principals, teachers and other education related personalities of Malaysia and likewise.